Knowledge acquisition, training, and the firm's performance: A theoretical model of the role of knowledge integration and knowledge options - Markus Hagemeister; Arturo Rodríguez Castellanos (European Research on Management and Business Economics (ERMBE), 2019)
This paper seeks to develop a theoretical model to explain the role of knowledge integration and knowledge options in the case of external knowledge acquisition via employee training. It considers types of knowledge acquired through specific or general training and heterogeneous or homogeneous production processes at companies. It also considers the possibility of opportunistic behaviour by trained employees. We propose key conditions that companies should consider when they acquire external knowledge by means of training. Insights are given into the process of and success conditions for dynamic value creation due to the adoption and the internal sharing of knowledge. Even at this early stage our theoretical model provides guidelines for decision-makers as to how to improve investments in training issues. The model leads to several propositions and provides a starting point for developing hypotheses that can be contrasted empirically in further research.
Keywords: M53; 650; Employee training; Knowledge integration; Knowledge options